2013
DOI: 10.1088/0004-637x/775/1/62
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a ∼300 Megaparsec Scale Under-Density in the Local Galaxy Distribution

Abstract: Galaxy counts and recent measurements of the luminosity density in the near-infrared have indicated the possibility that the local universe may be under-dense on scales of several hundred megaparsecs. The presence of a large-scale under-density in the local universe could introduce significant biases into the interpretation of cosmological observables, and, in particular, into the inferred effects of dark energy on the expansion rate. Here we measure the K−band luminosity density as a function of redshift to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
197
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(227 citation statements)
references
References 103 publications
26
197
3
1
Order By: Relevance
“…Altogether, the apparent detection of a local under density can be considered as a possible cause of the original tension between low and high redshift observational constraints discussed in [10,11,12,13,15], which as a solution also agree with the analysis of [19] where they proposed the existence of a local under-density to alleviate the tension in the determination of H 0 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Altogether, the apparent detection of a local under density can be considered as a possible cause of the original tension between low and high redshift observational constraints discussed in [10,11,12,13,15], which as a solution also agree with the analysis of [19] where they proposed the existence of a local under-density to alleviate the tension in the determination of H 0 .…”
Section: Discussionsupporting
confidence: 66%
“…Although simple extensions of the ΛCDM model were studied, not all of them alleviated the tension. In [19] the authors showed that the assumption of a large local under-density on radial scales of a few Mpc it is enough to alleviate such a tension.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the local galaxy luminosity density indicate that the local universe coincides with an extreme void. Based on Keenan et al (2013Keenan et al ( , 2014 . The values are very close to those of the CS Void.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations from 2MASS have suggested that there exists a galaxy underdensity in the Southern hemisphere (Keenan, Barger & Cowie 2013;Whitbourn & Shanks 2014), and we wish to test for the existence of this 'Local Hole' at optical wavelengths. Since VST ATLAS will also cover the Great Attractor region, this means that it can use the form of bright galaxy counts to search a large area in this direction for clusters and superclusters even behind Shapley 8.…”
Section: Atlas Science Aimsmentioning
confidence: 99%